The Polanyian Intellectual Legacy for the 21st century: Recent Japan-based Research on the Contributions of Karl Polanyi - Midori Wakamori (Journal of Economics / Keizaigaku Zasshi, 2018)
This paper presents a memorial to the great Hungarian economist Karl Polanyi, with special emphasis on recent Japanese scholarship. To begin with, I affirm that for Polanyi “fictitious commodities” and “fictitious commodity markets" were key institutions of market society. Next I consider his assertion that the Poor Law controversy played a crucial role in introducing a competitive labor market into Britain from the second half of the 18th century to the first half of the 19th century. Polanyi explained that during that period a “theory of self-responsibility for poverty and unemployment” emerged, as did the beginning of economic liberalism. Then I emphasize that in his thinking, the rise of fascism is related to the fatal errors of liberal economic policymaking. According to Polanyi, the austerity policies of economic liberalism, which subordinated people's interests to those of the financial sector and undermined efforts to maintain peace, had a destructive influence on the lives of the people living in deficit states and in the Western democracies. His analysis of economic liberalism and fascism remains useful for considering the emergence of bad populism' (which is antithetical to democracy and human freedom) in our own age. Finally, in this paper, I examine Polanyi's thoughts on human freedom
Keywords: Japan; POLANYI, Karl, 1886-1964; Polanyian approaches; austerity (economics); labor market; labour market

Housing Projects for Low-Income Groups and Modes of Economic Integration: A Comparative Study in Greater Cairo - Abouelmagd, Doaa; Kesteloot, Christian; Corijn, Eric (Tijdschrift voor Economische en Sociale Geografie (Journal of Economic & Social Geography), 2013)
The housing of low-income groups in Greater Cairo has always been difficult. However, the general shortage in housing supply is contrasting with the low occupancy rate of newly constructed public housing units. In contrast, despite their bad living conditions, informal settlements have a high occupancy rate. In order to analyse the reasons behind this contradiction, the paper compares four neighbourhoods ranging from formal and semi-informal to informal housing production and including one rehabilitation project. The livelihood conditions in each settlement are unravelled with the concept of modes of economic integration from Polanyi. For this purpose, semi-structured interviews were conducted and analysed with correspondence analysis. The findings indicate a preference among low-income groups for informal settlements because of three reasons: the advantages of geographical location, the nature of social networks and the strength of private redistribution systems, thus enabling an easier access to means of existence. The results and recommendations are further discussed in the paper.
Keywords: Egypt; Greater Cairo; housing rehabilitation; informal settlements; livelihood; living conditions; low-income housing; modes of economic integration; occupancy rates; poor people; public housing; redistribution; squatter settlements

The Making of Karl Polanyi's Economic Sociology. (In Japanese. With English summary.) - Wakamori, Midori (History of Economic Thought, 2010)
The main purpose of this paper is to understand Polanyi's research project after The Great Transformation. This includes his developing ideas on economic history and theory of economic institutions after 1947, when he came to Columbia University in New York. This paper deals mainly with Polanyi's new agenda, namely "the place of the economy in society" in the intellectual context of post World War II United States of America.
Keywords: Marxist; Sraffian; economic anthropology; economic sociology; history of economic thought since 1925: socialist; history of economic thought: individuals; social and economic stratification